2023
DOI: 10.7759/cureus.35925
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tobacco Smoking and Associated Risk Factors Among Public Sector Employees in Kuwait: A Cross-Sectional Study

Abstract: Introduction There needs to be more evidence about the tobacco products utilized by individuals who smoke and the primary determinants contributing to the development of smoking behavior. Our study aimed to assess the prevalence and factors associated with using one or more tobacco products among employees from various ministries in Kuwait. Methods A cross-sectional study was conducted among employees in different ministries in Kuwait from December 27, 2018, to January 3, 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, both cohort investigations demonstrated that 40% of female patients have a positive cigarette smoking history. An investigation of a non-trauma cohort has also shown that smoking is more common in males than in females [ 14 ]. The current study demonstrated that the positive cigarette smoking history proportion was greater with penetrating trauma than with blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…However, both cohort investigations demonstrated that 40% of female patients have a positive cigarette smoking history. An investigation of a non-trauma cohort has also shown that smoking is more common in males than in females [ 14 ]. The current study demonstrated that the positive cigarette smoking history proportion was greater with penetrating trauma than with blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that 62% of the 27 countries had significant impact on SDR. Several studies have illustrated country-specific evidence to identify the relationship between the two variables considering different dependent conditions like smoking status, socioeconomic status, age, gender and student attitudes towards smoking [ 24 26 ]. Those studies have incorporated countries like Hawaii, the United Arab Emirates, Kuwait, the US, Russia, and Denmark as the selected population of the study and have found that smoking can be a heterogeneous risk factor for the incidence of stroke in two ways: first, by directly causing damage to both the vascular system and its function.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is widely prevalent in Kuwait, and shisha smoking is as popular as cigarette smoking 5 . Shisha is one of the most common modalities used to indulge in tobacco products, especially among females, in Kuwait 6 . Furthermore, a self-reported questionnaire study about smoking behavior and beliefs among a non-random sample of Kuwaitis found that 45% smoked only waterpipe 7 .…”
Section: Introductionmentioning
confidence: 99%